End of history, Covid 19, and new Leviathan the broken communication between modernism and postmodernism - Vlajki, Emil (2021)
This work is about the spirit of Western civilization and its temptations. Drawing on Hegel's philosophy of history, the text explains why, until recently, this civilization was dominant over the rest of the world. The thing is that she understood the importance of rationality, subordinated all manifestations of life to her and especially, during capitalism (modernism), developed science and technology, and produced powerful weapons. Along the way, she incorporated all the significant achievements of other civilizations and peoples into her system of rationality. In this regard, Hegel says in the introduction to the Philosophy of History: "The only Thought which Philosophy brings with it to the contemplation of History, is the simple conception of Reason; that Reason is the Sovereign of the World; that the history of the world, therefore, presents us with a rational process." In other words, history is exclusively occupied with showing how Reason (Mind) comes to a recognition and adoption of the Truth. Of course, rationality is something that belongs to all civilizations and peoples, but other societies, for various reasons (geographical, climatic, religious, etc.) subordinated rationality to some other imperatives. Therefore, many of these communities were non-historical. Whatever it was, the West exploited its supremacy by colonizing other civilizations and destroying some. From the usual moral point of view, it is unacceptable, criminal. However, Hegel's philosophy, somewhat in Marx and Engels's interpretation, says something else. History makes sense. Its primary goal is to preserve humankind from anything that could destroy it, especially from various natural cataclysms and deadly diseases. The meaning of history is also its progress towards civil society as the realization of freedom and the end of history. This was only possible by adopting and practicing absolute rationality.
Ovo djelo govori o duhu zapadne civilizacije i njezinim iskušenjima. Oslanjajući se na Hegelovu filozofiju povijesti, tekst objašnjava zašto je donedavno ova civilizacija bila dominantna nad ostatkom svijeta. Stvar je u tome što je razumjela važnost racionalnosti, podredila sve manifestacije života njoj, a posebno, tijekom kapitalizma (modernizma), razvila znanost i tehnologiju i proizvela moćno oružje. Usput je u svoj sustav racionalnosti uključila sva značajna dostignuća drugih civilizacija i naroda. U tom smislu, Hegel u uvodu filozofije povijesti kaže: "Jedina misao koju filozofija donosi sa sobom u kontemplaciju povijesti je jednostavna koncepcija Uma; da je Um vladar svijeta; da nam povijest svijeta, dakle, predstavlja racionalan proces." Drugim riječima, povijest je isključivo okupirana pokazivanjem kako Um dolazi do priznanja i usvajanja Istine. Naravno, racionalnost je nešto što pripada svim civilizacijama i narodima, ali su druga društva, iz različitih razloga (geografskih, klimatskih, vjerskih itd.) podredila racionalnost nekim drugim imperativima. Stoga mnoge od tih zajednica nisu bile povijesne. Što god da je bilo, Zapad je iskoristio svoju nadmoć kolonizirajući druge civilizacije i uništavajući neke. Sa uobičajenog moralnog stajališta, to je neprihvatljivo, kriminalno. Međutim, Hegelova filozofija, donekle u Marxovoj i Engelsovoj interpretaciji, govori nešto drugo. Povijest ima svoj smisao. Njegov primarni cilj je sačuvati čovječanstvo od svega što bi ga moglo uništiti, osobito od raznih prirodnih kataklizmi i smrtonosnih bolesti. Smisao povijesti je i njegov napredak prema civilnom društvu kao ostvarenju slobode i kraja povijesti. To je bilo moguće samo usvajanjem i prakticiranjem apsolutne racionalnosti. Zašto oružje i nasilje? Apsolutna racionalnost, da bi bila povijesno učinkovita, morala je pokriti cijeli svijet.
Bibliografske bilješke na kraju teksta.
Summary ; Sažetak.
Keywords: Filozofija povijesti -- Dijalektika -- Komunikacija -- Modernizam -- Postmodernizam -- Međunarodni odnosi -- COVID-19; Hegel, Georg Wilhelm Friedrich